**Given:**

The sequence is
an+1=an1+an
. (1)

The first term of the sequence is
a1=2
.

**Calculation:**

Obtain the second term of the sequence.

Substitute 1 for *n* in equation (1).

a1+1=a11+a1

a2=a11+a1
(2)

Substitute 2 for
a1
in equation (2).

a2=21+2=23

Thus, the second term of the sequence is
a2=23_
.

Obtain the third term of the sequence.

Substitute 2 for *n* in equation (1).

a2+1=a21+a2

a3=a21+a2
(3)

Substitute
23
for
a2
in equation (3).

a3=231+23=233+23=25

Thus, the third term of the sequence is
a3=25_
.

Obtain the fourth term of the sequence.

Substitute 3 for *n* in equation (1).

a3+1=a31+a3

a4=a31+a3
(4)

Substitute
25
for
a3
in equation (4).

a4=251+25=235+23=27

Thus, the fourth term of the sequence is
a4=27_
.

Obtain the fifth term of the sequence.

Substitute 4 for *n* in equation (1).

a4+1=a41+a4

a5=a41+a4
(4)

Substitute
27
for
a4
in equation (4).

a5=271+27=237+23=29

Thus, the fifth term of the sequence is
a5=29_
.

Therefore, the first five terms of the sequence are
2,23,25,27,29
.